SILENCING AND SURVIVAL: THE POLITICS OF SPACE, GENDER, AND IDENTITY IN COLUM MCCANN’S ZOLI (2006) - Anchal Meena; Jha, Smita; Mishra, Sanjit Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In his novel Zoli (2006), Colum McCann intricately portrays the struggles of identity formation, building emotional intimacy, and fighting for survival. Zoli Novotna belongs to the marginalized Roma community that has experienced the systemic adversity perpetuated by the state. The text subtly explores the political exploitation faced by this community, which ultimately extends to the personal subjugation experienced by the titular character. Through her, McCann elucidates the inner conflicts of a young girl navigating the challenges of being Roma within the broader societal context and of identifying as a woman within her own patriarchal community. The article stems from this conflict. It studies the text from three apparently distinctive yet highly intertwined narratives. While the first narrative sheds light on the lived experiences of the Roma, offering insights into this academically ignored community, the second and third narratives delve into the complex power dynamics between the state and the Roma community, which has been manifested primarily in her subjecting experiences. As both a poet and a singer, she creates a space for exploring the multifaceted dimensions of the text. The paper argues that Zoli’s journey illustrates how personal and collective traumas are shaped by broader socio-political dynamics, reflecting the feminist adage that "the personal is political." By engaging with the intersections of identity, space, and power, the paper contributes to a deeper understanding of the complexities faced by marginalized communities in literature and society.